The acute physiological stress response to driving: A systematic review. - Michael Antoun; Kate M Edwards; Joanna Sweeting; Ding Ding (PLoS ONE, 2017)
Background The experience of driving has been suggested to be detrimental to health. One hypothesis is that each exposure elicits an acute stress response, and that repeated exposures may act as a chronic stressor. Objective The aim of this review is to evaluate and synthesise the evidence on whether driving elicits an acute physiological stress response. Methods Electronic databases, including CINAHL, PsycINFO and Medline, were searched for original articles written in English from database inception until March 2016. The inclusion criteria of this review included a quantitative examination of an acute physiological stress response to driving, in either on-road or simulated settings, compared to a comparison or control condition. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting criteria. Results A total of 27,295 abstracts were screened and 28 full-text manuscripts retrieved. Of these, seven articles met the inclusion criteria including four simulator studies and three on-road studies. All suggested a significant change in at least one physiological outcome, but the strongest evidence was for increases in urine catecholamine and cortisol after driving for long hours on-road; results on other outcomes are limited by the small number of studies or inconsistent findings. Conclusions Overall, these studies provided moderate evidence to suggest that driving for long hours elicits a stress response over an extended period of time. There is insufficient evidence that driving for a shorter period of time elicits an acute stress response, especially in real, on-road tasks. However, the limited number of studies, small sample sizes, heterogeneity in study objectives, methodologies and physiological outcomes limit conclusions. Future studies could be improved by recruiting a larger sample, utilizing modern stress markers such as heart rate variability, and primarily focusing on the acute physiological stress response to on-road driving.